RHEUMATIC DISEASES AND TUBERCULOSIS INFECTION IN CHILDREN AND ADULTS - G. V. Santalova; E. A. Borodulina; D. A. Kudlay; D. S. Badaeva; B. E. Borodulin; E. S. Gasilina (Туберкулез и болезни лёгких)
The authors summarized publications on the risk to develop tuberculosis during the treatment of rheumatic diseases with genetically engineered biologic drugs. The article describes the approaches to optimization of tuberculosis control activities in patients with rheumatic diseases: immunodiagnostics of latent tuberculosis infection and prevention of tuberculosis disease in the patients receiving genetically engineered biological drugs.